Perluasan Makna dan Variasi Kata Anjing Pada Generasi Milenial - Intan Rawit Sapanti; irwan suswandi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
The use of the word “anjing” by millennials today shows a variety of new meanings. Different context brought different variation that create semantics symptoms; change of meaning. The various functions of “anjing” and its variants range from expressing the expression of surprise, admiration, annoyance, greeting to show the familiarity. The purpose of this study, the authors want to describe the meaning and the variation of “anjing” used by millennials. There are 4 step of the research, i.e 1) the analysis of the lexical meaning, 2) the analysis of the contextual meaning, 3) the component analysis of the meaning, 4) the validation of data findings and the result obtained are the expansion of the meaning and variations of “anjing”. The result, the word “anjing” has experience an expansion of meaning, i.e. annoyed, angry, surprised, cursed, amazed, delicious, disappointed, did not expect and funny.Keywords: Anjing, change of meaning, semantics, millenials, variation